Unveiling the consequences of prejudice against muslim women: How the hijab can influence islamophobia perception, acculturation preferences and well-being - Rosa, Vanessa de Oliveira (2021)
In the interpretation of the Islamic culture, Muslim women have been placed, particularly, as one of the main objects of cultural differentiation. Restrictions on the use of clothing and religious symbols at work or in public spaces have continued to guide innumerous debates in the European Union (EU). The study in question investigated how islamophobia perception and different sub-dimensions of acculturation orientations (i.e., cultural maintenance, desire for contact) mediate the relationship between frequency of use of the hijab and well-being of Muslim immigrant women in Spain. Results indicated that the relationship between frequency of the use of hijab and well-being was mediated by islamophobia perception, suggesting that the more the participants wear the hijab, the more they perceived islamophobia and reported less well-being. Also, islamophobia perception was positively correlated to both the participant’s desire for contact and cultural maintenance. On the other hand, the participant’s acculturation preferences were not correlated to well-being.